Long-term effects on immunological, inflammatory markers, and HIV-1 reservoir after switching to a two-drug versus maintaining a three-drug regimen based on integrase inhibitors - Saborido-Alconchel, Abraham; Serna-Gallego, Ana; Trujillo-Rodriguez, María; Muñoz-Muela, Esperanza; Álvarez-Ríos, Ana I.; Lozano, Carmen; Llaves-Flores, Silvia; Espinosa, Nuria; Roca-Oporto, Cristina; Herrero, Marta; Sotomayor, Cesar; Gutierrez-Valencia, Alicia; et al. (Frontiers in Immunology, 2024)
Objective: To compare the long-term effects on immune parameters, inflammation, and HIV-1 reservoir after switching to a two-drug (2DR) versus maintaining an integrase inhibitor (InSTI)based three-drug regimen (3DR).Methods: Cross-sectional study in which HIV-1 treatment-naïve people started and maintained an InSTI-based 3DR or, at different times, switched to 2DR (dolutegravir or darunavir/cobicistat + lamivudine). CD4 + and CD8 + T-cell activation and exhaustion, plasma concentrations of hs-CRP, D-dimer, P-selectin, IL-1β, IL-6, TNF-α, IFN-γ, IP-10, sTNFR-I/II, MIP-1α/β, I-FABP, LBP, sCD14, sCD163, MCP-1, and cellular-associated HIV-1-DNA and -RNA were quantified by flow cytometry, different immunoassays, and droplet digital PCR, respectively. The U de Mann-Whitney test evaluated differences between 3DR and 2DR. Immune recovery was evaluated using a general linear model for repeated measures adjusted for different co-variables.Results: Fifty participants per group were included. The median time on 3DR was 82 months for the 3DR group and 30 months for the 2DR group, after which it switched to 2DR for a median of 57 months. We did not find differences between both groups in any of the parameters analyzed.Specifically, some values in 3DR and 2DR were hs-CRP, 0.92 mg/L (0.45-2.23) vs. 1.23 (0.61-2.38); D-dimer, 190.0 µg/L (150.0-370.0) vs. 190.0 (150.0-397.5); IL-6, 2.8 pg/mL (1.3-5.3) vs.3.2 (2.1-4.7); sCD14, 4.5 ng/mL (3.3-6.2) vs. 5.0 (3.6-6.1), respectively, all p ≥ 0.399.In the long term, switching to 2DR does not negatively affect immunologic parameters, inflammatory markers, or HIV-1 reservoir.